Antioxidant Supplementation among Chronic Obstructive Pulmonary Disease (COPD): Is it Necessary? - Pirabbasi, E.; Cheraghi, M. (Pakistan Journal of Nutrition, 2012)
The development of airflow limitation is related to inadequate antioxidant intake and hence dietary supplementation may be a beneficial therapeutic intervention. Antioxidants with good bioavailability or molecules that have antioxidant enzyme activity may not only protect cells against the direct injurious effects of oxidants, but may fundamentally alter the inflammatory events that play an important part in the pathogenesis of Chronic Obstructive Pulmonary Disease (COPD). We aimed to review highlights the role of antioxidant and antioxidant vitamins in respiratory health. This is a retrospective study which is reviewing twenty cross-sectional and nine interventional studies from years 1990 to 2007 which were journal publications on the benefits of antioxidants and antioxidant supplementation among COPD patients. The results and finding from reviewing the studies, revealed that antioxidant vitamins [e.g. Vitamin A, E, C and N-acetyl Cysteine (NAC)] had an important role in respiratory health and lung function.